The American president [videorecording (DVD)] - Reiner, Rob; Douglas, Michael, 1944-; Bening, Annette; Sheen, Martin; Fox, Michael J., 1961- (Distributed by Warner Home Video, 2008)
Widower Andrew Shepherd decides it's time to get back into the dating game, but there is one slight problem, he is the President of the United States. He falls for an environmental lobbyist and is lofted even more into the public eye.